EFEKTIVITAS BEKAM TERHADAP PENURUNAN TEKANAN DARAH SYSTOLE PADA PASIEN HIPERTENSI - Aris Setyawan, Wiwik Widia Astuti (AKPER Pemkab Purworejo, 2022)
Effectiveness of Cupping to Decrease Systole Blood Pressure in Hypertension Patients Abstract Background: Hypertension is a state of abnormal blood pressure in systole and diastole. High blood pressure can be managed with treatment namely non-pharmacologically such as cupping. Cupping is a treatment by suctioning the skin or certain parts to remove toxins in the body and plays a role in lowering blood pressure. Thus, researchers conducted further research, related to cupping in reducing systole blood pressure in hypertension patients. Methods: This study is a causal study with a quasi-experimental research design and a pre-post test with control design. The number of respondents was 32 respondents with 16 respondents as the experimental group and 16 respondents as the control group. Respondents were selected using simple random sampling techniques. The instruments in this study used blood pressure gauges (sphygmomanometers, stethoscopes and blood pressure results sheets). The data was analized by using the Wilcoxon test and the Mann-Whitney test. Result: The result of the data analysis showed that there were significant difference between pre-test and post-test in the experimental group with a p-value of 0,000 and there is no significant difference in the control group with a p-value of 0.317. Conclution: It can be concluded that cupping effect is used as a nursing intervention for systole blood pressure in hypertension patients in Posbindu PTM Wijaya Kusuma Taskombang Palbapang, Bantul District, Bantul Regency, Special Region of Yogyakarta. It is hoped that further researchers can conduct researches by adding variables or in different diseases.